Substance P in the anterior thalamic paraventricular nucleus: promotion of ethanol drinking in response to orexin from the hypothalamus. (29th July 2015) - Barson, Jessica R.; Poon, Kinning; Ho, Hui Tin; Alam, Mohammad I.; Sanzalone, Lilia; Leibowitz, Sarah F.
Abstract: The paraventricular nucleus of the thalamus (PVT) appears to participate in drug addiction. Recent evidence in rats shows that ethanol drinking is increased by orexin/hypocretin (OX) afferents from the hypothalamus, acting specifically in the anterior (aPVT) rather than posterior (pPVT) PVT subregion. The present study sought to identify neuropeptides transcribed within the PVT, which themselves might contribute to ethanol drinking and possibly mediate the actions of OX. We discovered that substance P (SP) in the aPVT can stimulate intermittent‐access ethanol drinking, similar to OX, and that SP receptor [neurokinin 1 receptor/tachykinin receptor 1 (NK1R)] antagonists in this subregion reduce ethanol drinking. As with OX, this effect is site specific, with SP in the pPVT or dorsal third ventricle having no effect on ethanol drinking, and it is behaviorally specific, with SP in the aPVT reducing the drinking of sucrose and stimulating it in the pPVT. A close relationship between SP and OX was demonstrated by a stimulatory effect of local OX injection on SP mRNA and peptide levels, specifically in the aPVT but not pPVT, and a stimulatory effect of OX on SP expression in isolated thalamic neurons, reflecting postsynaptic actions. A functional relationship between OX and SP in the aPVT is suggested by our additional finding that ethanol drinking induced by OX is blocked by a local NK1R antagonist administered at a sub‐threshold dose. These results, suggesting that SP in the aPVT mediates the stimulatory effect of OX on ethanol drinking, identify a new role for SP in the control of this behavior. Abstract : Intermittent‐access 20% ethanol drinking may involve neuropeptide communication between the hypothalamus and the anterior paraventricular thalamus (aPVT). Ethanol drinking is hypothesized to be promoted by orexin/hypocretin (OX) from the hypothalamus acting at the orexin 2 receptor (OX2R) on substance P (SP)‐containing neurons in the aPVT. Ethanol drinking has also been shown to increase levels of OX, which would further excite this aPVT pathway. In contrast, SP in the posterior paraventricular thalamus (pPVT) promotes sucrose intake.